(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
This article discusses the theoretical and pedagogical foundations of effective organization of environmental education among primary school students, teaching them to consciously approach environmental protection, as well as improving this process based on interdisciplinary integration.